2015
DOI: 10.3390/toxins7041174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of the Efficacy of Three Different Adsorbents against OTA-Induced Toxicity in Broiler Chickens

Abstract: The aim of our study was to determine the efficacy of three different adsorbents, inorganic (modified zeolite), organic (esterified glucomannans) and mixed (inorganic and organic components, with the addition of enzymes), in protecting broilers from the toxic effects of ochratoxin A in feed. Broilers were fed diets containing 2 mg/kg of ochratoxin A (OTA) and supplemented with adsorbents at the recommended concentration of 2 g/kg for 21 days. The presence of OTA led to a notable reduction in body weight, lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Santin et al (2002) reported similar observations when birds were given 2 mg/kg OTA along with 0.25% HSCAS in feed. Similarly, Nedeljkovic-Trailovic et al (2015) presented similar results in birds given OTA along with 2 g/kg modified zeolite. Regarding serum biochemical alterations, significant increase in creatinine, ALT and urea levels in OTA intoxicated birds has also been reported by many workers (Kubena et al, 1988;Bailey et al, 1989;Gentles et al, 1999;Stoev et al, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…Santin et al (2002) reported similar observations when birds were given 2 mg/kg OTA along with 0.25% HSCAS in feed. Similarly, Nedeljkovic-Trailovic et al (2015) presented similar results in birds given OTA along with 2 g/kg modified zeolite. Regarding serum biochemical alterations, significant increase in creatinine, ALT and urea levels in OTA intoxicated birds has also been reported by many workers (Kubena et al, 1988;Bailey et al, 1989;Gentles et al, 1999;Stoev et al, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…This process could potentiate the direct local toxic effect of the T-2 toxin and its active metabolites after enterohepatic recirculation, thus disrupting the protective effects of Minazel-Plus ® and Mycofix-plus ® . The lack of a full protective potential of Minazel-Plus ® and Mycofix-plus ® to completely prevent T-2 toxin intoxication may be explained by the fact that inorganic materials such as activated charcoal, clay, bentonite, and aluminosilicate (principally proposed to reduce the toxic effects of aflatoxins) [ 35 , 36 , 39 , 40 ], have a limited efficacy relative to other toxins [ 38 ]. Moreover, almost all inorganic adsorbents contain dioxin and heavy metals, which are toxic.…”
Section: Discussionmentioning
confidence: 99%
“…By providing the previously demonstrated mechanism of gastric toxicity induced by the T-2 toxin, an approach that supports the use of adsorbents seems to be rational. Numerous studies have shown that treatment with different adsorbents in clinical practice leads to a significant reduction and/or elimination of the adverse effects of varied mycotoxins [ 35 , 36 , 37 , 38 , 39 , 40 ]. In those studies, adsorbents, as substances unlikely to be absorbed from the intestine, have an exquisite potential to bind natural chemicals to themselves, thus preventing their absorption.…”
Section: Introductionmentioning
confidence: 99%
“…It causes a reduction in growth rate and feed consumption, poorer feed conversion and increased mortality (Nedeljković et al, 2015). Ochratoxicosis has been implicated in a diverse range of toxicological effects, including renal toxicity, mutagenicity, teratogenicity, neurotoxicity and immunotoxicity in both animals and human (O'Brien and Dietrich, 2005).…”
Section: Resultsmentioning
confidence: 99%